908 Personal Protective Equipment (PPE) Guidance During A Global Pandemic: A Statistical Analysis of National Perceived Confidence, Knowledge, And Educational Deficits Amongst U.K. Based Doctors. (4th May 2021) - Al-Hity, S; Bhamra, N; Kumar, R; Gupta, K; Howard, J; Jolly, K; Darr, A
Abstract: Introduction: March 11th, 2020 saw the World Health Organisation declare a global pandemic following the eruption of the novel coronavirus disease 2019. Unprecedented global demand for personal protective equipment (PPE) was complicated by limited availability and conflicting guidance from healthcare bodies. This study aimed to assess perceived confidence and knowledge of Public Health England's PPE guidance amongst doctors of varying specialties and grades. Method: A nationwide 11-point survey comprising of multiple-choice questions (MCQs) and a Likert scale assessing perceived confidence (1=not confident, 5=very confident) was disseminated to U.K. based doctors using multiple platforms. Results: Data collated from 697 respondents revealed average perceived confidence was low. Notably, 59% felt they had received insufficient education regarding up-to-date guidance, with 81% advocating further training. Anaesthetics and ophthalmology were the highest and lowest scoring specialties in knowledge based MCQs, achieving 59% and 31% respectively. Subsequent statistical analysis revealed significant differences between specialties." Conclusions: Ensuring consistency in published PPE guidance and education can develop doctor's confidence and knowledge of appropriate PPE use. The absence of a unified consensus and global education regarding the use of PPE poses significant ramifications for patient and healthcare professional (HCP) safety whilst risking further depletion of already sparse resources.